KEPUASAN WARGA BELAJAR TERHADAP PENGELOLAAN BIMBEL SMART GANESHA PEKANBARU - Pani Sari, Olvi Sepko Pani Sari Sepko; Natuna, Daeng Ayub Natuna Ayub Natuna; Maemunaty, Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problems of this study is how high the students’ satisfaction on the management of the Smart Ganesha Bimbel Pekanbaru. The purpose of this study was to determine the level of students’ satisfaction toward the management of Smart Ganesha Bimbel Pekanbaru. The benefits of this research are to increase the satisfaction of students’ taking course in Bimbel Smart Ganesha. This is a descriptive study with a quantitative approach. The population is 130 people. The samples in this study using stratified random sampling technique. The instrument used in this study was a questionnaire containing 50 items in the statement of students’ satisfaction taking course at Smart Ganesha Bimbel Pekanbaru, with indicator 1) feelings of pleasure, 2) a feeling of relief, and 3) a feeling of happy. Alternative answers each item has a statement strongly agree categories (SS) was scored 5, agrees (S) was given a score of 4, less amenable (KS) was given a score of 3, disagree (TS) was given a score of 2, and strongly disagree (STS) given a score of 1. The survey results revealed that the satisfaction of the students’ taking course in Smart Ganesha Bimbel Pekanbaru was very high. This evidenced are from the exposure data summary that are: (1) Feeling pleased with the choice of answers strongly agree (SS) and agree (s) obtained percentage score of 99.44%, (2) Relief with a choice of answers strongly agree (SS) and agree (S) obtained scores percentage of 87.94%, (3) feeling happy with the choice of answers strongly agree (SS) and agree (s) obtained percentage score of 85.81%. This means that managers of Smart Ganesha Bimbel Pekanbaru have served students’ to learn well and as expected. Key words: Satisfaction, students’, Bimbel